Initial Oral English Communication Needs of Learners in the Business English Classroom - Paramudia Paramudia; Hadina Habil (Journal of Education and Learning (EduLearn), 2015)
The aim of the study was to investigate the level of effectiveness and initial oral English communication (OEC) needs of Indonesian learners when using OEC to perform the learning activities in the Business English (BE) classroom at Business Administration Departement of the Politeknik Negri Ujung Pandang (PNUP) in Makassar Indonesia. Conceptually, the needs of learners cover aspect of "want, Necessity, and lack" that were developed and used as research indicators of this study. The sample of this study was 159 Business Administration Departement of PNUP learners. The findings discovered that the level of effectiveness of learners of using OEC when performing the learning activities both under academic and business contexts in the BE classroom was moderate. This study also found that initial needs of learners relating to specific skills from the aspect of lack, necessaity, and want both under academic and business contexts in the BE classroom should be prepared before taking BE subject. Finally, the study suggested investigating further both the target needs and learning needs of learners in the BE classroom.